Sistem Informasi Kelayakan Pemberian Pinjaman dengan Metode Analitycal Hierarchy Process (AHP) - Nurhadi nurhadi; Dede Yusminandar; Khabibillah; Muhammad Khaerudin (LPPM Universitas Potensi Utama, 2022)
The analysis process of selecting the feasibility of providing loans to creditors, sometimes they still use calculations and analyze estimates. This results in inaccurate decision making. In this study the authors make a Decision Support System as a basis that aims to provide decision support to the administration to determine customers in determining lending based on the data submitted by the prospective customer on the registration form. So that the lender is more efficient and effective in their work, prospective customers can simulate the amount that will be obtained through a web-based online application. The AHP (Analitycal Hierarchy Process) method will process the data and analyze it so that it issues the criteria ranking value. The information generated is in the form of information that has been manipulated by the system to determine whether or not members are eligible for a loan, as well as the appropriate amount based on the members' income and guarantees listed in the application form. This system can also be actually used by users and can be used easily because in its development it uses a prototype method which in its development involves users